2022
DOI: 10.3390/ijms23073561
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine Mitigates Inflammation-Related Oxidative Stress in BV-2 Cells by Inducing a Pre-Adaptive Response

Abstract: Neuroinflammation and microglial activation, common components of most neurodegenerative diseases, can be imitated in vitro by challenging microglia cells with Lps. We here aimed to evaluate the effects of agmatine pretreatment on Lps-induced oxidative stress in a mouse microglial BV-2 cell line. Our findings show that agmatine suppresses nitrosative and oxidative burst in Lps-stimulated microglia by reducing iNOS and XO activity and decreasing O2− levels, arresting lipid peroxidation, increasing total glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 79 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…Under normal conditions, Nrf-2 is localised in the cytoplasm and the nuclear translocation of Nrf-2 is inhibited by Keap1. However, under oxidative stress conditions, Nrf-2 is detached from Keap1 and translocated into the nucleus to regulate the expression of antioxidant proteins such as HO-1 [ 56 , 57 ]. Chronic inflammation has been reported in HO-1 deficient models [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, Nrf-2 is localised in the cytoplasm and the nuclear translocation of Nrf-2 is inhibited by Keap1. However, under oxidative stress conditions, Nrf-2 is detached from Keap1 and translocated into the nucleus to regulate the expression of antioxidant proteins such as HO-1 [ 56 , 57 ]. Chronic inflammation has been reported in HO-1 deficient models [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of cytotoxic molecules such as hydrophobic bile acids and supraphysiological levels of bilirubin in the lung tissue is proposed to be involved in the pathogenesis of oxidative stress and lung injury in cholestasis [21]. The effects of the biogenic amine AGM on oxidative stress biomarkers are widely investigated in various experimental models [33,46,[73][74][75][76]. The direct radical scavenging properties of AGM have been mentioned in previous studies [77,78].…”
Section: Agmatine Ameliorates Lung Inflammationmentioning
confidence: 99%
“…There are also reports of inflammatory cell infiltration in human cases of cholestasis-induced lung injury [21]. On the other hand, previous studies revealed that AGM acts as an excellent anti-inflammatory agent [46,50,[82][83][84][85][86][87]. A big part of the anti-inflammatory properties of AGM seems to be mediated through the inhibitory effects of this amine on the enzyme inducible nitric oxide synthase (iNOS) [84].…”
Section: Agmatine Ameliorates Lung Inflammationmentioning
confidence: 99%
See 2 more Smart Citations